Partial identification of heteroskedastic structural VARs: Theory and Bayesian inference - Helmut Lütkepohl; Fei Shang; Luis Uzeda; Tomasz Woźniak (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
We consider structural vector autoregressions identified through stochastic volatility. Our focus is on whether a particular structural shock is identified by heteroskedasticity without the need to impose any sign or exclusion restrictions. Three contributions emerge from our exercise: (i) a set of conditions under which the matrix containing structural parameters is partially or globally unique; (ii) a statistical procedure to assess the validity of the conditions mentioned above; and (iii) a shrinkage prior distribution for conditional variances centred on a hypothesis of homoskedasticity. Such a prior ensures that the evidence for identifying a structural shock comes only from the data and is not favoured by the prior. We illustrate our new methods using a U.S. fiscal structural model.
Keywords: C11; C12; C32; E62; 330; Identification Through Heteroskedasticity; Stochastic Volatility; Non-centred Parameterisation; Shrinkage Prior; Normal Product Distribution; Tax Shocks